1982
DOI: 10.1063/1.33910
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in p−p elastic scattering at high energies

Abstract: Some recent data on polarization in p-p elastic scattering are briefly surveyed and their characteristics reviewed. A new 28 GeV/c measurement of A, the analyzing power is presented. A few interesting theories are also briefly discussed. We plan more measurements of A soon and planto measure ANN when the polarized beam comes on at the A.G.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…(16) Multiple studies have demonstrated the formation of secondary BrC through laboratory experiments. (9,(17)(18)(19)(20)(21)(22)(23)(24)(25) Laboratory-based chamber experiments suggest that a variety of factors impact the light absorption of SOA, including precursor composition (volatile organic compounds, VOC), (17) oxidants (e.g., hydroxyl radical, OH; nitrogen oxides NO X ), (20) aging, (9) and seed acidity. (25) These studies conclude that the SOA derived from the photo-oxidation of anthropogenic aromatic VOCs (e.g., toluene) has stronger light absorption than typical biogenic (e.g., α-pinene) SOA reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…(16) Multiple studies have demonstrated the formation of secondary BrC through laboratory experiments. (9,(17)(18)(19)(20)(21)(22)(23)(24)(25) Laboratory-based chamber experiments suggest that a variety of factors impact the light absorption of SOA, including precursor composition (volatile organic compounds, VOC), (17) oxidants (e.g., hydroxyl radical, OH; nitrogen oxides NO X ), (20) aging, (9) and seed acidity. (25) These studies conclude that the SOA derived from the photo-oxidation of anthropogenic aromatic VOCs (e.g., toluene) has stronger light absorption than typical biogenic (e.g., α-pinene) SOA reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…In Figures 3 and 4 comparisons of numerical results with experimental one, that presented in paper [4] are shown. The stress-strain curves are for element 1 (see Figure 1).…”
Section: Numerlcal Results and Discussionmentioning
confidence: 99%
“…Equations (4) and ( 6 ) constitute field equations of the thermomechanical rate problem. They must be satlsfied identically at any time, in the whole volume of the investigated structure V and should be augmented with appropriate boundary and initial conditions:…”
Section: R $ ( a ; ) ( L -Z )mentioning
confidence: 99%
See 2 more Smart Citations